Comparative analysis on virtual private network in the internet of things gateways - Mohd Idzaney, Zakaria; Mohd Natashah, Norizan; Muammar, Mohamad Isa; Mohd Faizal, Jamlos; Muslim, Mustapa (Institute of Advanced Engineering and Science, 2022)
A virtual private network (VPN) connects a private network to the internet, primarily the public network, through a secure tunnel. Using a local area network (LAN) segment, users can send and receive data from their colleagues in different locations on the network. The development of VPN allows users to gain access to company applications and databases. Therefore, data can be transmitted through a secure tunnel without the need to configure port forwarding for the internet of things (IoT) gateway, allowing users to access it from any location in the world. A method such as dataplicity and pitunnel was examined to compare with the conventional setting. This research paper examines the current deployment of VPN connections in IoT gateways, discussing their characteristics, benefits, and drawbacks, as well as comparing them. The advantage of this method is that the IoT gateway is always accessible and has internet connectivity, which is a significant benefit. Dataplicity is a more trustworthy option because they offer excellent assistance for both the backend and frontend environments.